Phase formation, dielectric and magnetic properties of bismuth ferrite-lead magnesium niobate multiferroic composites - R. Wongmaneerung (2018)
Binary multiferroic composites (1-x)BiFeO3-xPb(Mg1/3Nb2/3)O3(BF-PMN; x = 0.0-50 wt%) were fabricated through a traditional ceramic process. The effect of the PMN contents on the phase assemblage, microstructure, dielectric and magnetic properties of the samples were investigated by X-ray diffraction (XRD), scanning electron microscope (SEM), LCR meter and vibrating sample magnetometer (VSM), respectively. The results indicate that all composites show that perovskite structure and PMN phase is compatible with the BF phase. The microstructure displays the mix phases between BF, PMN, Bi-rich BF and Fe-rich BF phases. Dielectric anomalies of these composites are totally different from BiFeO3single phase. Moreover, the dielectric constant is found to increase as the content of PMN decreases. Magnetic transition temperatures are in the range of 270-440 °C. Interestingly, the M-H hysteresis loop measurements indicated that all composites exhibited weak ferromagnetism behavior at room temperature. The maximum remanent magnetization Mris observed for x = 30 wt% and then decreases when the PMN content is more than 40 wt%. © 2014 Elsevier B.V. All rights reserved.